The impact of MFG-E8 in chronic pancreatitis: potential for future immunotherapy? - D'Haese, Jan Goesta; Demir, Ihsan Ekin; Kehl, Timo; Winckler, Jannik; Giese, Nathalia; Bergmann, Frank; Giese, Thomas; Büchler, Markus W.; Friess, Helmut; Hartel, Mark; Ceyhan, Güralp Onur (BMC gastroenterology, 2013)
The glycoprotein MFG-E8 mediates phagocytic clearance of apoptotic cells and influences the pathogenesis and progression of inflammatory diseases. MFG-E8 was shown to attenuate the progression of inflammation and to improve survival in septic rats. Accumulating evidence suggests an immunomodulatory link between MFG-E8 and the pro-inflammatory chemokine fractalkine, which may determine the severity of pain, fibrosis, and inflammation in chronic pancreatitis (CP).